An investigation into the reaction of bifunctional reactive dye at various pH levels - (:unkn) unknown (SOC DYERS AND COLOURISTS PERKIN HOUSE, 1996)
The bifunctional reactive dye Sumifix Supra Blue BRF, which has two different reactive groups (sulphatoethylsulphone and monochlorotriazine), was stored for 1 h at various pH before dyeing. Corresponding experiments were carried out with individual sulphatoethylsulphone and monochlorotriazine reactive dyes. The pH values of the solutions were set firstly by using free inorganic acid or base at 20 degrees C and secondly by using various buffer solutions at 20 degrees C and 60 degrees C. The bifunctional dye always had relatively less unfixed dye than the corresponding monofunctional dyes at the various pH values examined. It is suggested that with this type of bifunctional reactive dyes on dyeing cellulose the sulphatoethylsulphone has the greater role to play in dye fixation.